Facile synthesis of gamma-ketophosphonates by an intermolecular stetter reaction onto vinylphosphonates - Patra, Atanu; Bhunia, Anup; Biju, Akkattu T. (Organic Letters, 2014)
The atom-economic and practical N-heterocyclic carbene (NHC) catalyzed Stetter reaction for the synthesis of gamma-ketophosphonates by the reaction of aromatic aldehydes with vinylphosphonates is reported. The NHC derived from N-mesitylimidazolium salt (IMes) was an effective catalyst for this transformation, and the products were formed in moderate to good yields.